SISTEM PEREKONOMIAN MASYARAKAT MELAYU SUKU BONAI DI KECAMATAN BONAI DARUSSALAM KABUPATEN ROKAN HULU - Indres Novri Yanti; Yasnel (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This article discusses the economic system in Bonai, Bonai Darussalam sub-district, Rokan Hulu Regency. The purpose of this article is to discuss the economic issues and challenges faced by the Bonai community in order to strengthen their traditional economic system in the context of their development in the era of globalization. The research method used is field study. According to the study's findings, the majority of the Bonai people, who are predominantly from the Bonai Malay ethnic group, tend to support two economic systems: agriculture and fisheries. The problems faced by the community in Bonai include market access related to a lack of insight, lack of knowledge and skills, and so on. Although the Bonai Malay community is active in agricultural and fishing activities, they still have the desire to sell and exchange goods with people outside the Bonai region.